2012
DOI: 10.1097/ajp.0b013e3182274018
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Auricular Acupuncture for Chronic Low-back Pain

Abstract: Findings of this study showed that a main RCT is feasible and that 56 participants per group would need to be recruited, using multiple recruitment approaches. AA was safe and demonstrated additional benefits when combined with exercise for people with CLBP, which requires confirmation in a fully powered RCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 25 publications
3
64
0
Order By: Relevance
“…The type of pain included perioperative pain ( n = 9), acute pain ( n = 7), and chronic pain ( n = 6). The treatment duration ranged from one treatment (AA) to weekly AA treatment for up to 6 weeks [24]. The most popular acupoints selected for treatment were corresponding points ( n = 20), shenmen ( n = 17), and subcortex (also called dermis) ( n = 8).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The type of pain included perioperative pain ( n = 9), acute pain ( n = 7), and chronic pain ( n = 6). The treatment duration ranged from one treatment (AA) to weekly AA treatment for up to 6 weeks [24]. The most popular acupoints selected for treatment were corresponding points ( n = 20), shenmen ( n = 17), and subcortex (also called dermis) ( n = 8).…”
Section: Resultsmentioning
confidence: 99%
“…Among these 13 trials, two studies [20, 43] used a 0–100 scale to measure pain, while the eleven other studies used a 0–10 scale. Seven studies reported statistically significant pain relief of auricular therapy compared to the sham group [20, 21, 32, 34, 36, 39, 41, 43], while six studies found no significant difference in pain relief between auricular therapy and the sham control [24, 26, 27, 29, 31, 32]. Among the 13 trials, auricular therapy was found to be a significant method of pain relief when compared to the sham or control group (SMD = − 1.59,  95%  CI  [−2.36, − 0.82], P = 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that have examined the sustained effects of auricular therapy for pain relief have varied in duration from 1 session 47 to up to 6 months, 48 and their findings are limited by small sample sizes. 37,38 In our studies using APA to treat CLBP, 1 week of APA reduced pain intensity by 45%, 39 and 4 weeks of therapy achieved even more pain relief (75% reduction), which was maintained at 1-month follow-up.…”
Section: Auricular Pressing Timementioning
confidence: 99%
“…[88][89][90][91][92][93][94][95] In addition to traditional acupuncture, several modified acupuncture methods have been used in the treatment of CLBP, including scalp acupuncture, laser acupuncture, auricular acupuncture, Hegu acupuncture, motion style acupuncture, and electroacupuncture of the spinal nerve root. [96][97][98][99][100][101] Acupuncture, both manual and electroacupuncture, showed significant effects on pain reduction compared with a control group in an RCT (n=50) of acupuncture once a week for eight weeks. The decrease in pain intensity remained at three and six month follow-up assessments (P<0.05).…”
Section: Chronic Neck and Shoulder Painmentioning
confidence: 99%